Cardiomyocyte-restricted MIAT deletion is sufficient to protect against murine myocardial infarction - Taiki Hayasaka; Satoshi Kawaguchi; Marisa N. Sepúlveda; Jian-peng Teoh; Bruno Moukette; Tatsuya Aonuma; Meena S. Madhur; Ankit A. Desai; Suthat Liangpunsakul; Simon J. Conway; Il-man Kim (Cell Death Discovery)
Abstract Myocardial infarction-associated transcript (MIAT), an intergenic long noncoding RNA (lncRNA), is conserved between rodents and humans and is directly linked to maladaptive cardiac remodeling in both patients and mouse models with various forms of heart failure (HF). We previously reported attenuation of cardiac stress, apoptosis, and fibrosis in a murine model of myocardial infarction (MI) with global MIAT ablation. Our transcriptomic profiling and mechanistic studies further revealed MIAT-induced activation of maladaptive genes, such as Hoxa4, Fmo2, Lrrn4, Marveld3, and Fat4. However, the source of MIAT and its contribution to MI and HF remain unknown. In this study, we generate a novel cardiomyocyte (CM)-specific MIAT conditional knockout mouse model, which exhibits improved cardiac function after MI. We further report that CM-specific MIAT ablation is sufficient to reduce cardiac damage, apoptosis, and fibrosis following chronic MI. Mechanistically, CM-specific MIAT deletion in mice leads to decreased expression of proapoptotic and pathological profibrotic genes, such as p53, Bak1, Col3a1, Col6a1, Postn, and Snail1 after chronic MI. These results enable us to begin to dissect cell-specific contributions to MIAT signaling and bolster the idea that MIAT plays a direct pathological role in CMs after MI.